Dysfunctional institutions, social trust, and governance in areas of limited statehood - Risse, Thomas; Börzel, Tanja (2015)
Abstract: Areas of limited statehood where the state is absent or dysfunctional are rarely ungoverned or ungovernable spaces. The provision of rules and regulations as well as of public goods and services - governance - does not necessarily depend on the existence of functioning state institutions. How can this be explained? This article makes two claims. First, we identify functional equivalents to state institutions that fail to govern hierarchically. Second, we focus on informal institutions based on social trust that are endogenous to areas of limited statehood. Personalized social trust among community members enables actors to overcome collective action problems, enhancing the legitimacy of governance actors. The main challenge in areas of limited statehood, which are often characterized by social heterogeneity and deep social and cultural cleavages (particularly in post-conflict societies), is to move from personalized to generalized trust in "imagined communities" despite dysfunction